Money, not morale: The impact of desires and beliefs on private investment in photovoltaic citizen participation initiatives. (10th January 2017) - Fleiß, Eva; Hatzl, Stefanie; Seebauer, Sebastian; Posch, Alfred
Abstract: A transition towards renewable energy production is one proposed solution as one means of reducing greenhouse gas emissions. In this regard, photovoltaic citizen participation initiatives are a cornerstone in fostering the diffusion of renewables allowing for active citizen engagement. This article investigates the drivers behind people's decision to participate in two selected Austrian citizen participation initiatives in the field of photovoltaics based on a survey of 870 (potential) adopters. In addition to commonly used indicators, variables assessing both – people's desires, (their goals or 'preferences' with respect to energy autonomy, environmental protection, financial aspects, etc.), and their beliefs (how likely they think their participation in a citizen participation initiative in the field of photovoltaics will help them achieve these goals) are also included in the analysis. The findings show that people's desires are not decisive in deciding on PV participation, and that financial beliefs are the main driver behind joining such an initiative. This focus on financial gain clearly poses a risk in any attempted transition towards renewable energy production, as it indicates that adopters may withdraw from participation as soon as a more attractive investment opportunity becomes available. It also indicates that subsidized feed-in tariffs are likely to be essential in any long-term transition policy. Highlights: Citizen participation initiatives enable bottom-up engagement in energy transition. Investigating individuals' drivers to adopt using Logit regression analysis. We differentiate between desires and beliefs in the initiatives' specific impacts. Adoption is predominantly driven by financial, not environmental beliefs. PV-CPIs in Austria depend on continued feed-in tariffs.